If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2(x + -1) = 11 Reorder the terms: 5 + -2(-1 + x) = 11 5 + (-1 * -2 + x * -2) = 11 5 + (2 + -2x) = 11 Combine like terms: 5 + 2 = 7 7 + -2x = 11 Solving 7 + -2x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2x = 11 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 11 + -7 -2x = 11 + -7 Combine like terms: 11 + -7 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| 5.7=-0.6 | | 5(x+2)+38=-3x | | 2p+5q+3p+q= | | w+2/3=2w+1/5 | | v^2-13v+40=0 | | .7(x+60)+.5x=78 | | 8y+2(-1/4-2y)=3/2 | | 2(2x-3)=2(3x-2)/4 | | -9y-1=-8y-4 | | 1/7-5/2y-1/6y | | x/2-x+6/7=6 | | 0.22-0.03(x+2)=-0.04(3-x) | | 17-13=x/-5 | | 25x-2=40+4 | | 2x(2x-4)=0 | | 4.72f-0.5=-61.6f-8 | | 2.1k=9.66 | | ((2x-7)/x)=((x-2)/5) | | 7-3/4c=65 | | -8x+9x-13x= | | 4-3x=8(1-x) | | -7-3=9x+5-8x | | .3(y+8)+8=.16(9y-24)-4 | | 7(x-2)+3x=6x+18 | | t/12=3 | | -10+22=m-6 | | y=5+12 | | 5y+2+4y=112 | | -(5x-7)-(4x-4)+8=-8(x-3)-(8x+9)+8 | | 2l-3y=36-6y | | 3k-4/2=5 | | 3b-5=2b+1 |